1996
DOI: 10.1152/ajpheart.1996.270.1.h121
|View full text |Cite
|
Sign up to set email alerts
|

Failure of prolonged exercise training to increase red cell mass in humans

Abstract: The purpose of this study was to investigate the time-dependent effects of long-term prolonged exercise training on vascular volumes and hematological status. Training using seven untrained males [age 21.1 +/- 1.4 (SE) yr] initially consisted of cycling at 68% of peak aerobic power (VO2peak) for 2 h/day, 4-5 days/wk, for 11 wk. Absolute training intensity was increased every 3 wk. Red cell mass (RCM), obtained using 51Cr, was unchanged (P > 0.05) with training (2,142 +/- 95, 2,168 +/- 86, 2,003 +/- 112, and 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…The fact that trained athletes have an elevated TBV and relatively normal Hct values suggests that at least in the males, the PV adaptation persists and RCV is increased. However, several studies, including our own (Shoemaker et al 1996) have not been able to document increases in RCV with vigorous training conducted for up to 11 weeks. If RCV can be elevated to the level suggested in trained athletes, it would appear that a much more vigorous and sustained exposure to exercise is needed.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The fact that trained athletes have an elevated TBV and relatively normal Hct values suggests that at least in the males, the PV adaptation persists and RCV is increased. However, several studies, including our own (Shoemaker et al 1996) have not been able to document increases in RCV with vigorous training conducted for up to 11 weeks. If RCV can be elevated to the level suggested in trained athletes, it would appear that a much more vigorous and sustained exposure to exercise is needed.…”
Section: Discussionmentioning
confidence: 73%
“…The eect of training on RCV is not as clear. Although earlier studies have reported increases in RCV, recent studies using more accepted measurement procedures, with independent assessments of PV and RCV, have been unable to document changes, at least in response to training periods that have extended for up to 11 weeks and where 2 h of cycle exercise conducted ®ve to six times per week represented the training stimulus (Green et al 1991;Shoemaker et al 1996). Based on the inability of cycle training to increase RCV, two contradictory interpretations appear apparent, namely that the higher vascular volumes that are characteristic of the trained athlete are indeed an inherent characteristic of the trained athlete, or that the training stimulus was inappropriate for inducing the adaptations in RCV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for assessing tHb in elite athletes is that Xuctuations in tHb above a certain magnitude (yet to be determined) could be indicative of doping. Although tHb can increase with training in combination with altitude exposure (Brugniaux et al 2006), it seems that tHb is stable (Eastwood et al 2008) and is not inXuenced much by brief periods of training (Green et al 1991;Shoemaker et al 1996). Data from longitudinal studies are scarce, but in active healthy subjects the assessment of tHb over 100 days showed variation of approximately 2% (Eastwood et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3). In contrast, a compelling weight of evidence indicates that exercise training does not increase RBC mass 38 , and further that highly trained humans might actually evidence a mild reduction in haematocrit 39 . The single report that a transient increase in [EPO] occurred 31 h following marathon running may have been the result of that particular event causing dehydration and an extended period of exercise-induced decreases in renal blood flow 17 .…”
Section: Effects Of Exercise On Plasma [Epo]mentioning
confidence: 99%